KEDUDUKAN KHULUK DALAM PERSPEKTIF UNDANG-UNDANG PERKAWINAN INDONESIA DAN FIKIH ISLAM (Analisis Putusan Pengadilan Agama Pasir Pengaraian, nomor 273/Pdt.G/2015/PA.Ppg) - Nouvan Moulia (Prodi Ilmu Hukum, Universitas Teuku Umar, 2018)
Marriage is the inner bond between a man and a woman as husband and wife in order to form a sakinah family, mawaddah, wa rahmah. However, under certain circumstances the marriage may end with a divorce suit filed by the wife, usually the lawsuit is filed because the wives are no longer able to bear the behavior of her husband who has exceeded the limit of patience. In this research, the writer tries to analyze one of the decision of the Religious Court about the divorce and the position of the decision according to Islamic jurisprudence perspective, the decision to be analyzed is the decision of Religious Court of Pasir Pengaraian numbered 273/Pdt.G/2015/PA.Ppg. This research is a normative-empirical legal research, that is research done by reviewing written regulations and its aspects. The approach used in this research is the approach of legislation, conceptual approach, and comparative approach. From this research note that the divorce lawsuit contained in the KHI is not entirely the same as the divorce lawsuit contained in the UUP and PP 9/1975. According to the juristic law the consequences of divorce due to khuluk differ from divorce because taklik talak, either from the way it works to the legal consequences. Meanwhile, according to KHI different how it works but the same due to the law.Keywords: Divorce suit, khuluk, taklik talak, iwad